Global maximum power point tracking for photovoltaic systems under partial and complex shading conditions using a PID based search algorithm (PSA) - Azad, Md Adil; Sarwar, Adil; Tariq, Mohd; Bakhsh, Farhad Ilahi; Ahmad, Shafiq; Mohamed, Adamali Shah Noor; Islam, Md Rasidul (IET renewable power generation, 2025)
In scenarios of partial shading, the effectiveness of power transmission within a photovoltaic system experiences a notable decline, potentially leading to hotspots within the photovoltaic array. While incorporating bypass diodes can mitigate this challenge, it may lead to numerous power peaks along the power–voltage ( P – V ) characteristics, thus complicating the task of maximum power tracking. Addressing this issue, using metaheuristic algorithms for maximum power point tracking (MPPT) offers promising outcomes by circumventing convergence towards local power peaks and easing the computational strain on the microcontroller. This study presents a fresh approach to MPPT technique utilizing the proportional–integral–derivative‐based search algorithm to effectively identify the MPP under varying partial shading conditions. Compared to existing methods, the proposed algorithm demonstrates superior performance in power tracking efficiency, tracking time, stability with fewer fluctuations, and achieving higher maximum power output. Evaluation against state‐of‐the‐art algorithms like particle swarm optimization and JAYA confirms the effectiveness of the proposed MPPT technique. MATLAB/Simulink software‐based analysis and its validation using real‐time analysis from the typhoon based hardware‐in‐the‐loop (HIL‐402) emulator support its efficacy.